Grade 4 Bilingual Mathematics Workbook (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
This study delves into the results and implications of a study focused on the mathematics competence of Grade 4 learners.  The study explores various competencies, including visualizing, reading, writing, estimating, and problem-solving, as benchmarks for developing bilingual workbook instructional material.  The preliminary mathematics competence assessment revealed a low mastery level, with notable variation in different competencies.  Specifically, the respondents exhibited higher competence in reading and writing numbers up to one hundred thousand.  However, the overall math proficiency was found to be below the OECD mean score, as evidenced by the Program for International Student Assessment (PISA) 2018 report. The respondents' competencies were assessed through a pre-test and an intervention to improve their mathematical skills.  Notable variations were observed in different competencies, with some showing low mastery levels and others average or moving towards mastery levels.  After the intervention, a modest improvement was observed in the overall mathematics competence of the respondents, with an emphasis on enhanced visualizing skills.  Despite this improvement, specific competencies, particularly those related to division and multi-step problem-solving, still presented challenges. A paired sample t-test demonstrated a significant difference between pre-test and post-test performance, indicating the effectiveness of the bilingual instructional intervention.  These findings align with prior research highlighting the positive impact of localized and contextualized instructional materials on academic performance.  This study underscores the significance of bridging the transition from mother-tongue-based instruction to English through adapted learning materials. In conclusion, this study sheds light on the mathematics competence of Grade 4 learners, highlighting both their strengths and areas requiring improvement.  The findings underscore the significance of tailored instructional interventions in enhancing students' mathematical abilities.  As facilitated by the bilingual workbook, the transition from mother-tongue-based instruction to English instruction has demonstrated its effectiveness in positively impacting learners' mathematical performance.  While challenges persist in specific competencies, the overall improvement the post-intervention indicates the potential for further enhancement through focused interventions. While the study's scope is limited to Grade 4 mathematics competence and a specific instructional approach, its implications extend to broader educational contexts.  The principles of personalized instruction, gradual language transition, targeted intervention, localized materials, and ongoing assessment hold value in enhancing learning outcomes across subjects and grade levels.  This study serves as a steppingstone for educators, researchers, and policymakers to consider innovative and effective strategies for improving learning experiences and academic performance.
Keywords: bilingual mathematics workbook; pre-experimental study; mathematics competence; grade four learners